Channel length effect on the saturation current and the threshold voltages of CNTFET - Ani, Mohd Hanafi; Muhamad Ali, Abu Hanifah; Mohamed, Mohd Ambri (IEEE, 2014)
Carbon nanotubes (CNTs) are such promising material in future microelectronic devices due to their great property in conductivity, mechanical strength and light weight. Field effect transistor (FET) has already come to its most maximum efficiency because of their reduced size leads to decrease in their capability in conducting electric. It is interested to embed ballistic electron transfer capability of CNTs on FET. In this study, direct growth method of CNTs was employed to attach it on FET electrodes with various terminal gaps. The results show that CNTFET has successfully fabricated, with averaged saturation currents always lowest at the channel size of 15μm. While their highest measured threshold voltage value is 4.291 V at 15 μm gap. This phenomenon is attributed to the change of CNTs’ chirality, which apparently changes the metallic type of CNTs to the semiconducting CNTs.